Registry-based Diabetes Risk Detection Schema for the Systematic Identification of Patients at Risk for Diabetes in West Virginia Primary Care Centers - Baus, Adam (American Health Information Management Association, 2013)
Approximately 466,000 West Virginians, or about 25 percent of the state population, have prediabetes and are at high risk for developing type 2 diabetes. Appropriate lifestyle intervention can prevent or delay the onset of type 2 diabetes if individuals at risk are identified and treated early. The West Virginia Diabetes Prevention and Control Program and the West Virginia University Office of Health Services Research are developing a systematic approach to diabetes prevention within primary care. This study aims to demonstrate the viability of patient registry software for the analysis of disparate electronic health record (EHR) data sets and standardized identification of at-risk patients for early detection and intervention. Preliminary analysis revealed that of 94,283 patients without a documented diagnosis of diabetes or prediabetes, 10,673 (11.3 percent) meet one or more of the risk criteria. This study indicates that EHR data can be repurposed into an actionable registry for prevention. This model supports meaningful use of EHRs, the Patient-Centered Medical Home program, and improved care through enhanced data management.